Ostial vs. wide area circumferential ablation guided by the Ablation Index in paroxysmal atrial fibrillation - Sousa, Pedro A. (2023)
Pulmonary vein isolation (PVI) guided by the Ablation Index (AI) has shown high acute and mid-term efficacy in the treatment of paroxysmal atrial fibrillation (AF). Previous data before the AI-era had suggested that wide-area circumferential ablation (WACA) was preferable to ostial ablation. However, with the use of AI, we hypothesize that ostial circumferential ablation is non-inferior to WACA and can improve outcomes in paroxysmal AF. Methods and results Prospective, multicentre, non-randomized, non-inferiority study of consecutive patients were referred for paroxysmal AF ablation from January 2020 to September 2021. All procedures were performed using the AI software, and patients were separated into two different groups: WACA vs. ostial circumferential ablation. Acute reconnection, procedural data, and 1- year arrhythmia recurrence were assessed. During the enrolment period, 162 patients (64% males, mean age of 60 ± 11 years) fulfilled the study inclusion criteria—81 patients [304 pulmonary vein (PV)] in the WACA group and 81 patients (301 PV) in the ostial group. Acute PV reconnection was identified in 7.9% [95% confidence interval (CI), 4.9–11.1%] of PVs in the WACA group compared with 3.3% (95% CI, 1.8–6.1%) of PVs in the ostial group [P < 0.001 for non-inferiority; adjusted odds ratio 0.51 (95% CI, 0.23–0.83), P = 0.05]. Patients in the WACA group had longer ablation (35 vs. 29 min, P = 0.001) and procedure (121 vs. 102 min, P < 0.001) times. No significant difference in arrhythmia recurrence was seen at 1- year of follow-up [11.1% in WACA vs. 9.9% in ostial, hazard ratio 1.13 (95% CI, 0.44–1.94), P = 0.80 for superiority]. Conclusion In paroxysmal AF patients treated with tailored AI-guided PVI, ostial circumferential ablation is not inferior to WACA with regard to acute PV reconnection, while allowing quicker procedures with less ablation time.